A low-latency sub-micron resolution stripline beam position monitoring system for single-pass beamlines - Burrows, P; Bett, DR; Blaskovic Kraljevic, N; Christian, G; Davis, MR; Perry, C; Apsimon, R; Constance, B; Gerbershagen, A; Resta Ĺopez, J (2012)
A low-latency, sub-micron resolution stripline beam position monitoring system has been developed for use in single-pass beamlines. The fast analogue front-end signal processor is based on a single-stage RF down-mixer and is combined with an FPGA-based system for digitisation and further signal processing. The system has been deployed and tested with beam at the Accelerator Test Facility at KEK. Performance results are presented on the calibration, resolution and stability of the system. A detailed simulation has been developed that is able to account for the measured performance. Copyright © 2012 by IEEE.